Surgical accuracy, function, and quality of life of simultaneous versus staged bilateral Total hip Arthroplasty in patients with Osteonecrosis of the femoral head - Seung-Chan Kim; Young-Wook Lim; Woo-Lam Jo; Dong-Chul Park; Jin-Woo Lee; Won-Woo Kang; Yong-Sik Kim (BMC Musculoskeletal Disorders, 2017)
Abstract Background The optimal surgical option for patients requiring bilateral hip replacement remains controversial. The purpose of this study was to compare surgical accuracy; functional outcome and health-related quality of life; and prosthetic-related complications and revision surgery of a simultaneous bilateral total hip arthroplasty (THA) with those of a staged bilateral THA with an interval between procedures <12 months. Methods A total of 123 unselected consecutive patients (mean age, 43.3 years) who underwent bilateral THAs for osteonecrosis of the femoral head (ONFH) with a minimum follow-up of two years (mean, 60.2 months) were studied retrospectively; 63 simultaneous procedures served as a test group and 60 staged procedures served as a control group. Results The mean postoperative leg-length discrepancy (LLD) and the percentage of patients who had an LLD >3 mm were significantly lower in the simultaneous group (P < 0.001 and P = 0.001, respectively). A higher number of cups within the safe zones, a higher correction rate, and a lower failure rate for the cup placement in the second-operated hip were also identified in the simultaneous group. The mean Harris hip score, EuroQol-5D index, and EuroQol-visual analogue scale score were all better in the simultaneous group at the latest follow-up (P < 0.001, in all comparisons). We found that the simultaneous procedure was associated with a lower incidence of postoperative prosthetic-related complications and revision surgery. Conclusions We suggest that bilateral ONFH could be treated with a simultaneous THA rather than a staged THA to achieve a better surgical outcome.